The Effect of the Hypertrophy Virus (MdSGHV) on the Ultrastructure of the Salivary Glands of Musca domestica (Diptera: Muscidae) - Molina Palacios, D (J Insect Sci, 2021)
The salivary glands of insects play a key role in the replication cycle and vectoring of viral pathogens. Consequently, Musca domestica (L.) (Diptera: Muscidae) and the Salivary Gland Hypertrophy Virus (MdSGHV) serve as a model to study insect vectoring of viruses. A better understanding of the structural changes of the salivary glands by the virus will help obtain a better picture of the pathological impact the virus has on adult flies. The salivary glands are a primary route for viruses to enter a new host. As such, studying the viral effect on the salivary glands is particularly important and can provide insights for the development of strategies to control the transmission of vector-borne diseases, such as dengue, malaria, Zika, and chikungunya virus. Using scanning and transmission electron microscopic techniques, researchers have shown the effects of infection by MdSGHV on the salivary glands; however, the exact location where the infection was found is unclear. For this reason, this study did a close examination of the effects of the hypertrophy virus on the salivary glands to locate the specific sites of infection. Here, we report that hypertrophy is present mainly in the secretory region, while other regions appeared unaffected. Moreover, there is a disruption of the cuticular, chitinous lining that separates the secretory cells from the lumen of the internal duct, and the disturbance of this lining makes it possible for the virus to enter the lumen. Thus, we report that the chitinous lining acts as an exit barrier of the salivary gland.